Perilaku Ekonomi Perspektif Islam - M. Asy’ari (Al-Ulum, 2010)
This paper examines the economic behavior according to Islamic ethics. In economic theory, human behavior deals with four issues: production, distribution, service and consumption. There are four things assessed in Islamic ethics, four things related to the purpose of human life, the concept of good luck, property rights, and employment. The main argument proposed in this article is that Islam does not rule out the existence and worldly possessions, as long as they do not ignore the life hereafter. The purpose of life and human life is to gain happiness in this world and the hereafter as well. Therefore, ethics of Islam appreciate the professional as an integral part of religious orders.